University graduation dependent on family's wealth, ability and social status - Tim Ehlers (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2011)
This paper presents a model showing an incentive for a group of people to vote for higher tuition fees, even if these fees have no quality effect. The incentive is based on a non-monetary influence on utility, namely the social status or prestige of graduating. The basic assumption is that the higher the prestige is, the lower the number of people studying. In a static equilibrium, it is shown that a group of wealthier and more able people can exist that attempts to prevent others from studying.
Keywords: I22; J24; H52; 330; Studienfinanzierung; Studierende; Soziale Schicht; Bildungsökonomik; Theorie